Experimental assessment of a myocyte-based multiscale model of cardiac contractile dysfunction. (7th November 2018) - Lascano, Elena C.; Felice, Juan I.; Wray, Sandra; Kosta, Sara; Dauby, Pierre C.; Cabrera-Fischer, Edmundo I.; Negroni, Jorge A.
Highlights: A multiscale model of the cardiovascular system was built based on a human myocyte model. The effects of halothane, an anesthetic that at high doses elicits acute cardiac dysfunction, were simulated in the myocyte and analyzed at the myocyte, ventricular and circulatory levels. The multiscale model effectively reproduced contractile and hemodynamic dysfunction in sheep induced by an overdose of halothane. Abstract: Cardiac contractile dysfunction (CD) is a multifactorial syndrome caused by different acute or progressive diseases which hamper assessing the role of the underlying mechanisms characterizing a defined pathological condition. Mathematical modeling can help to understand the processes involved in CD and analyze their relative impact in the overall response. The aim of this study was thus to use a myocyte-based multiscale model of the circulatory system to simulate the effects of halothane, a volatile anesthetic which at high doses elicits significant acute CD both in isolated myocytes and intact animals. Ventricular chambers built using a human myocyte model were incorporated into a whole circulatory system represented by resistances and capacitances. Halothane-induced decreased sarco(endo)plasmic reticulum Ca 2+ (SERCA2a) reuptake pump, transient outward K + (Ito ), Na + -Ca 2+ exchanger (INCX ) and L-type Ca 2+ channel (ICaL ) currents, together with ryanodine receptor (RyR2) increased open probability (Po ) and reduced myofilament Ca 2+ sensitivity, reproduced equivalent decreased action potential duration at 90% repolarization and intracellular Ca 2+ concentration at the myocyte level reported in the literature. In the whole circulatory system, model reduction in mean arterial pressure, cardiac output and regional wall thickening fraction was similar to experimental results in open-chest sheep subjected to acute halothane overdose. Effective model performance indicates that the model structure could be used to study other changes in myocyte targets eliciting CD.